Architectural renderings - Schillaci, Fabio (Berlin DOM Publishers, 2010)
The rendering is the most potent means of communicating an architectural design. It provides a complete image of a building in its planned setting. Unlike a physical or computer model, an elevation or plan, it speaks in a direct and accessible visual language that will enable any viewer to immediately picture the architect s vision. The potency of the rendering is clearly understood by architects and clients alike. Major architectural practices now commission specialist studios to produce finished renderings of their buildings in order to effectively sell their designs to their clients, while clients also invest in renderings to convince the wider public of their vision for large scale architectural projects. Whereas traditionally the rendering was an architectural drawing enlivened by watercolour washes, contemporary renderings are produced in a wide range of media and formats with the explic
Keywords: THEROY, PRACTICE, NOTES; GRAPHICS AND DRAWINGS (GRP/DRW)